Methicillin Potentiates the Effect of Gentamicin on Methicillin-Resistant Staphylococcus aureus - Hemmer, Robert J. P. (1979)
Methicillin-resistant Staphylococcus aureus (MRSA) strains show an unusual type of resistance at 37°C; only a small subpopulation of cells is resistant to the β-lactam antibiotics. Incubation in the presence of methicillin (MET), however, results in the emergence of a homogenous population highly resistant to MET. The purpose of the present study was to determine whether MET, despite its lack of killing effect on MRSA, would promote the bactericidal effect of gentamicin (GM), as demonstrated for MET-susceptible strains of S. aureus. Eleven epidemiologically distinct strains of MRSA were incubated with MET at various concentrations, in the presence or absence of sub-bactericidal concentrations (1/5 or 1/10 of the minimal bactericidal concentration) of GM, and tested for the synergistic action of both antibiotics by three different methods. Population analysis of the 11 strains in the presence of high concentrations of MET showed that the addition of GM at 1/5 or 1/10 of its minimal bactericidal concentration resulted in marked killing of the 11 strains. Time-kill curves obtained with 32 μg of MET per ml and GM at 1/5 or 1/10 of its minimal bactericidal concentration confirmed this synergistic killing at 24 h. These results were further documented by the checkerboard method on two strains. We conclude that the synergism between MET and GM, previously demonstrated for MET-susceptible S. aureus, holds true for MRSA as well and that it can be demonstrated at sub-bactericidal concentrations of GM.